OPTIMIZING LOCAL OWN-SOURCE REVENEU THROUGH HOTEL AND RESTAURANT TAX SECTOR IN MALANG CITY DURING COVID-19 PANDEMIC - Narapraja, Awalludzin Kusuma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
This research aims to find out the policy of optimizing Local Own-Source Revenue in Malang City through Hotel and Restaurant Tax Sector in Malang City during Covid-19 Pandemic. In this research, the researcher took role as the instrument in data collection. The method used in this research was qualitative descriptive and the data used were data of Local Own-Source Revenue of Malang City in 2016-2020 and the data of hotel and restaurant tax gain in 2016-2020. From the results of this research, some findings were found such as first, there is decrease of Local Own-Source Revenue gain in Malang City from 2019 to 2020, especially in Hotel and Restaurant tax sector. Second, there is decrease of hotel and restaurant tax sector because of hotel and restaurant closing caused by Covid-19 pandemic. Third, the government of Malang City and Malang City Revenue Agency made policy of alleviating the hotel and restaurant business owners impacted by Covid-19 pandemic. Overall, Local Own-Source Revenue of Malang City is still not optimized maximally yet.Keywords: Optimizing Local Own-Source Revenue, Hotel Tax, Restaurant Tax